(untitled) (Научни трудове на УНСС, 2019)
The problem of this article concern the lack of Defence Resource Planning (DRP) for the future environment of the Internet of Things(IoT). This paper shows the aspect in the DRP in Bulgaria and the probable change in the environment of IoT. The article provides data, cases and examples for comparison. The author shows DRP in Bulgaria in some details, that concerns the analyzed object. Study explains the connection between IoT and DRP. There are some basics about ERP. In this article finds a place the main difference between DRP and ERP. The paper acknowledges the threats and the change of the threats in the IoT. In this article are used several methods for quality analyses that include documentary, process, system case study and analogy methods. This article is one of the first with economic and management approach on this topic – smart devices (that communicate independently through IoT) and their significance for DRP. According to the hypotheses, the main author’s conclusion is that the implementation of IoT in DRP will have a major impact on the US-centric military oriented states.